The MASIV survey: spectroscopic identifications of compact radio sources. Issue Volume 9:Issue S304(2013) (25th July 2014) - Pursimo, T.; Ojha, R.; Jauncey, D.; Lovell, J.; Dutka, M.; Bignall, H.; Macquart, J.-P.; Rickett, B.; Kedziora-Chudczer, L.; Koay, J. Y.
Abstract: Interstellar scintillation (ISS) has been shown to be primarily responsible for the short term intraday variability (IDV) exhibited by extragalactic sources at centimeter wavelengths (e.g. Bignall et al . 2006 and references therein). For a source to scintillate its angular size must be comparable to that of the first Fresnel zone (Narayan 1992) which implies microarcsecond angular sizes for screen distances of tens to hundreds of parsecs. This has the potential to probe within a few light months of the central black hole (Bignall et al . 2006). The aim of the Microarcsecond Scintillation-Induced Variability (MASIV) survey was to provide a catalogue of at least a hundred AGNs that vary on timescales of hours to days to provide the basis of detailed studies of the IDV population drawn from a well-defined sample.